Content vs. age: perceived credibility of older and young adult eyewitnesses with confidence inflation. Issue 5 (28th May 2021) - Iida, Ryosuke; Itsukushima, Yukio
ABSTRACT: With populations aging rapidly across the world, an increasing amount of attention is being paid to how older eyewitnesses are perceived by jurors. Current literature reports mixed results. While some papers suggest that negative age stereotypes undermine the perceived credibility of older eyewitnesses, others indicate that the perceived credibility of eyewitnesses, regardless of age, is determined by the contents of their testimonies. To solve this tension in the literature, we completed two experiments that manipulated eyewitness age (21 vs. 74 years old) and confidence consistency (consistent vs. inconsistent) to uncover the situations in which older eyewitnesses were and were not comparable to younger adult eyewitnesses. If negative age stereotypes influence older eyewitness credibility, the effects of negative age stereotypes would be observed more clearly when the older eyewitness was inconsistent than when they were consistent. This is because inconsistent older eyewitnesses match negative age stereotypes (e.g. older eyewitnesses are incompetent). However, eyewitness age did not prove to have a significant effect on the perception of eyewitness credibility. As a result, we propose that eyewitness credibility is determined by confidence consistency. The implications for activating the mechanism of negative age stereotypes and practical support for older eyewitnesses are discussed.